THE RELATIONSHIP BETWEEN JOB SATISFACTION AND EMPLOYEE PERFORMANCE: AN HRM LITERATURE PERSPECTIVE - Ja'far Amiruddin; Al-Amin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Job satisfaction and employee performance are two crucial aspects that are interrelated in human resource management. Research shows that there is a positive correlation between job satisfaction and employee performance, where satisfied employees tend to show higher productivity, stronger levels of commitment, and lower absenteeism. However, the literature also indicates that this relationship is influenced by various other factors, such as intrinsic motivation, personal values, and work environment conditions. Therefore, management needs to consider the broader context to ensure sustainable improvements in employee performance. Contemporary approaches emphasise the importance of an integrated strategy, which not only increases job satisfaction but also creates a supportive work environment to achieve optimal performance. An effective HRM strategy will take into account both psychological and structural aspects to maximise employee performance and thus have a positive impact on the whole organisation.